Extraction of palm kernel shell derived pyrolysis oil by supercritical carbon dioxide: Evaluation and modeling of phenol solubility - Chan, Y.H. (Elsevier Ltd, 2018)
The extraction and recovery of value-added chemical compounds, such as phenolic compounds present in bio-oil has been a vital subject of study recently. In this work, the extraction of bio-oil using supercritical carbon dioxide (sc-CO2) with particular interest in apparent solubility of phenol (a major chemical compound in pyrolysis oil) was evaluated at various temperatures (50, 60 and 70 °C) and pressures (30, 35 and 40 MPa). Highest extraction yield of bio-oil was obtained at 70 °C and 40 MPa. The phenol content in the extracted bio-oils were also studied and reported. As a preliminary study, the apparent solubility data of phenol in sc-CO2 was successfully modeled using the values from the correlation of Chrastil, Adachi & Lu and Bartle models. The model parameters for these equations were determined and reported in this work. It was found that Chrastil, Adachi & Lu and Bartle models produced satisfactory correlations on the solubility of phenol in sc-CO2, with AARD values of 1.51, 6.52 and 1.85, respectively. © 2018 Elsevier Ltd